South Africa: An Important Soybean Producer in Sub-Saharan Africa and the Quest for Managing Nematode Pests of the Crop - Gerhard Engelbrecht; Sarina Claassens; Charlotte M. S. Mienie; Hendrika Fourie (Agriculture, 2020)
With an increase in the global population, a protein-rich crop like soybean can help manage food insecurity in sub-Saharan Africa (SSA). The expansion of soybean production in recent years lead to increased land requirements for growing the crop and the increased risk of exposing this valuable crop to various pests and diseases. Of these pests, plant-parasitic nematodes (PPN), especially Meloidogyne and Pratylenchus spp., are of great concern. The increase in the population densities of these nematodes can cause significant damage to soybean. Furthermore, the use of crop rotation and cultivars (cvs.) with genetic resistance traits might not be effective for Meloidogyne and Pratylenchus control. This review builds on a previous study and focuses on the current nematode threat facing local soybean production, while probing into possible biological control options that still need to be studied in more detail. As soybean is produced on a global scale, the information generated by local and international researchers is needed. This will address the problem of the current global food demand, which is a matter of pressing importance for developing countries, such as those in sub-Saharan Africa.